The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1038/nm.3705
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic control in diabetes is restored by therapeutic manipulation of cytokines that regulate beta cell stress

Abstract: In type 2 diabetes, hyperglycemia is present when an increased demand for insulin, typically due to insulin resistance, is not met as a result of progressive pancreatic beta cell dysfunction. This defect in beta cell activity is typically characterized by impaired insulin biosynthesis and secretion, usually accompanied by oxidative and endoplasmic reticulum (ER) stress. We demonstrate that multiple inflammatory cytokines elevated in diabetic pancreatic islets induce beta cell oxidative and ER stress, with inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
261
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 221 publications
(302 citation statements)
references
References 68 publications
29
261
6
Order By: Relevance
“…New approaches or improved agents are required to suppress oxidative stress. For example, we have found that the cytokine, IL‐22, drives a robust natural anti‐oxidant programme in secretory cells,113 including respiratory epithelial cells, potentially providing a more effective mechanism to protect cells from both environmental and intrinsically‐generated ROS/RNS.…”
Section: Therapeutic Approaches To Resolve Oxidative and Er Stress Inmentioning
confidence: 99%
“…New approaches or improved agents are required to suppress oxidative stress. For example, we have found that the cytokine, IL‐22, drives a robust natural anti‐oxidant programme in secretory cells,113 including respiratory epithelial cells, potentially providing a more effective mechanism to protect cells from both environmental and intrinsically‐generated ROS/RNS.…”
Section: Therapeutic Approaches To Resolve Oxidative and Er Stress Inmentioning
confidence: 99%
“…In prediabetes and the early phases of diabetes, insulin hypersecretion is evident with progressive serum hyperinsulinaemia and hyperproinsulinaemia. Similarly, mice fed high fat diets show serum hyperinsulinaemia and hyperproinsulinaemia, and their islets hypersecrete insulin on ex vivo glucose challenge (Hasnain et al 2014). In chronic ER stress, quality control mechanisms that retain misfolded proteins in the ER are relaxed or overwhelmed, allowing misfolded proteins to move to the Golgi and be packaged for secretion .…”
Section: Intrinsic Er Functionsmentioning
confidence: 99%
“…As discussed above, the chronic ER stress that develops with prediabetes and early diabetes is associated with increasing serum insulin, which is typically accompanied by decreasing intracellular stores of insulin in b-cells (Hasnain et al 2014). Under these conditions, the b-cells are manufacturing large quantities of insulin under suboptimal conditions within the ER and almost continuously secreting some insulin, although secretion still surges post-prandially.…”
Section: Increased Insulin Biosynthesismentioning
confidence: 99%
“…There is some evidence that secreted insulin from high-fat diet-induced obese C57BL/6 (HFDIO) mice islets is less functional in insulin bioassays (10), such that functional quality of secreted insulin deserves more attention. Furthermore, within the same study, treatment of the HFDIO mice with the anti-inflammatory interleukin-22 improved the degree of hyperinsulinemia, the pattern of glucose-stimulated insulin release, and the quality of the insulin released, suggesting that pharmacological interventions aimed at reducing islet b-cell inflammation may have the potential to reverse proinsulin processing defects (10). Insulin hypersecretion has been proposed as a causative factor for type 2 diabetes and obesity, as well as a risk factor for islet b-cell failure, such that therapies to prevent this may be protective (11)(12)(13)(14).…”
Section: Diabetesdiabetesjournalsorgmentioning
confidence: 99%